PENGEMBANGAN FLIPBOOK BERBASIS CONTEXTUAL TEACHING AND LEARNING UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS PESERTA DIDIK KELAS VII SMP - Hani, Fadillah (Jurnal Edukasi dan Penelitian Matematika, 2025)
This research is a development research that aims to produce a valid and practical Contextual Teaching and Learning (CTL) based flipbook on the material of linear equations and inequalities of one variable in class VII SMP. The research used the Research and Development (R&D) method with the Plomp model, which includes preliminary research, and prototyping phase. Validation was carried out by two mathematics lecturers and a mathematics educator, while the practicality test was carried out on VII grade students of SMP Negeri 3 X Koto Singkarak. The instruments used are interviews, questionnaires of students' opinions, validation questionnaires and practicality questionnaires. Based on the results of the study, it shows that the CTL-based flipbook meets the criteria of being very valid with a validation level of 94.41% and very practical with a practicality level of 91.64%. This flipbook is designed to provide an interactive learning experience by integrating text, images, videos, and relevant contextual questions. The flipbook is expected to be a relevant teaching material innovation to improve the quality of mathematics learning in the digital era.Keywords– Flipbook, Contextual Teaching and Learning, Mathematical Problem Solving, Linear One Variable Equations and Inequalities, Blended Learning.